Why do people pay for useless advice? Implications of gambler's and hot-hand fallacies in false-expert setting - Nattavudh Powdthavee; Yohanes E. Riyanto (Institute for the Study of Labor (IZA), 2012)
We investigated experimentally whether people can be induced to believe in a non-existent expert, and subsequently pay for what can only be described as transparently useless advice about future chance events. Consistent with the theoretical predictions made by Rabin (2002) and Rabin and Vayanos (2010), we show empirically that the answer is yes and that the size of the error made systematically by people is large.
urn:nbn:de:101:1-201301212288
Keywords: C91; D03; 330; gambler's fallacy; hot-hand; random streak; expertise; information; Verhaltensökonomik; Informationsverhalten; Sachverständige; Glücksspiel